Ligand exchange processes on the solvated zinc cation II. *[Zn(H2O)4L]2+•2H 2O with L = NH3, NH2(CH3), NH(CH3)2, and N(CH3)3 - Alzoubi, Basam; Puchta, Ralph; van Eldik, Rudi (Australian Journal of Chemistry, 2010)
Water-exchange mechanisms for the complexes [Zn(H2O) 4L]2+2H2O, L =NH3, NH 2CH3, NH(CH3)2, and N(CH 3)3, have been studied by density functional theory calculations (B3LYP/6311+G**). The water-exchange reactions follow an associative (A) pathway involving formation of a six-coordinate intermediate [Zn(H2O)5L]2+H 2O. Electronic and steric effects of the amine ligands influence the activation barrier and the stability of the six-coordinate intermediate. © CSIRO 2010.
CRIS-Team Scopus Importer:2026-01-22